Systematic Review and Meta-Analysis of the Efficacy and Safety of Telavancin for Treatment of Infectious Disease: Are We Clearer? - Chuan, Junlan; Zhang, Yuan; He, Xia; Zhu, Yuxuan; Zhong, Lei; Yu, Dongke; Xiao, Hongtao (Frontiers in Pharmacology, 2016)
Telavancin is approved to treat complicated skin and skin structure infections, hospital-acquired and ventilator-associated bacterial pneumonia caused by Staphylococcus aureus. A previous meta-analysis of randomised controlled trials suggested that it might be an alternative to vancomycin in cases of difficult-to-treat meticillin-resistant Staphylococcus aureus infections. We did a meta-analysis including new trials to access the efficacy and safety of telavancin.